Dietary differences in health sciences students (Journal of Health Sciences, 2025)
Introduction: The impact of nutrition on human health has become a central topic in modern research. The Mediterranean diet, rich in fruits, vegetables, fish, whole grains, and olive oil, has been associated with a lower risk of cardiovascular diseases. However, the effects of non-Mediterranean diets, particularly among students, remain insufficiently explored. This study aimed to examine differences in the dietary habits of health sciences students in two cities in Bosnia and Herzegovina (Mostar and Sarajevo) and Split, Croatia.Methods: A cross-sectional descriptive study was conducted between February and November 2024, including 473 students (Mostar: 125, Sarajevo: 230, Split: 118). Dietary habits were assessed using a validated food frequency questionnaire and the Mediterranean Diet Adherence Screener. Statistical analysis included Pearson’s chi-square test, with significance set at p < 0.05.Results: Students from Split showed significantly higher adherence to Mediterranean dietary habits, including greater consumption of vegetables (p = 0.009), fish (p = 0.035), legumes (p = 0.036), and tomato sauce (p = 0.022). Students in Sarajevo reported the highest intake of sugary drinks (p < 0.01), while those in Split consumed the least margarine and cream-based fats (p = 0.003). No significant differences were found in fruit consumption.Conclusion: Given the importance of diet in preventing chronic diseases, targeted nutrition education programs are needed to promote healthier eating habits among students. Future research should explore the underlying causes of these dietary differences and their long-term health implications.